Pillar[5]arene/imidazolium based [n]rotaxanes - Langer, Philipp (2019)
Molecular machines and motors play a key role in numerous biological processes. Nature has thrown down the gauntlet regarding complexity and function of these systems. Over the last decade advances in synthetic and supramolecular chemistry have enabled chemists all over the world to make significant progress towards conquering the realm of nanomachines. At the forefront of this are mechanically interlocked molecules (MIMs), which have also added an additional dimension to various fields of both experimental and theoretical chemistry. The potential applications of molecular machines is undoubtedly immense and bridging the gap between the current generation of molecular machines and state of the art systems found in nature bears great reward. MIMs commonly feature members of the key macrocycle families. One of the most prominent recently discovered families of macrocycles are pillar[n]arenes. Their potential in the synthesis of MIMs is of great interest and is currently subject to substantial investigation. Unlike in macroscopic machines where energy is typically converted to motion, in the realm of nanomachines Brownian motion results in continuous movement of the molecular components relative to each other. Therefore, one of the key challenges emerging in the field of molecular machines is controlling the motion of mechanically interlocked components relative to each other. A typical example of this are two station molecular shuttles, in which a macrocycle continuously moves back and forth between two identical stations. Metal coordination to a series of pillar[5]arene/bis-imidazolium [2]rotaxanes through the formation of metal-carbene bonds facilitates a new strategy to restrict the shuttling motion in two station molecular shuttles. Whilst pillar[5]arene exhibits fast shuttling along the entire bis-imidazolium axle in the parent [2]rotaxanes, Ag(I)- or Pd(II)-coordination to the imidazoliums through the formation of an N-heterocyclic carbene results in restricted motion. Ag(I)-coordination can be reversed to obtain the parent species and is a potential starting material for further transmetalation reactions with a range of other metals. The asymmetric Pd(II)-coordination to only one imidazolium is achieved through fine tuning of the spacer length, separating the two imidazolium units. In order to synthesise MIMs with specific functions for applications, it is necessary to develop a synthetic toolbox which allows the straightforward combination of different components to produce systems with desirable and predictable properties in high yields under mild conditions. Furthermore, it has to be possible to build up more complex [n]rotaxanes and include supramolecular building blocks such as porphyrins, carbazoles, NIs and BODIPYs. Such a toolbox approach is developed by demonstrating that the three constituents of a [n]rotaxane (the rod, the macrocycle and the stopper group) can all be functionalised to contain an array of desirable moieties. The complex interplay of components in MIMs and the significant impact threading can have on the overall properties of the system is demonstrated by fluorescence measurements, finding that regulation of the fluorescent response can be achieved through certain combinations of macrocycle and rod substitution. The toolbox developed herein is employed in the synthesis of [2]rotaxanes with handcuff topology, which allows molecules to be loosely connected whilst positioning them in close proximity. This strategy is demonstrated by the production of rylene diimide dimers, connected through pillar[5]arene/imidazole mechanical bonds. The spectroscopic and electrochemical investigation of these compounds enables a rare insight into the manner in which these compounds interact and demonstrates some intriguing new properties. In particular, the perylene diimide dimer handcuff displays fascinating characteristics such as excimer emission and an unusual visible absorption profile, showing the formation of a radical anion -dimer upon double reduction. Interesting interactions in a naphthalene diimide dimer and a mixed perylene/naphthalene diimide dimer are also observed, the second of which demonstrates the superior flexibility of this synthetic approach. The effect of Pd(II)-coordination to the imidazoliums of the handcuffs on the overall properties of the system is evaluated, showing small but important changes in the way the rylene cores interact. The synthetic strategy described within this thesis facilitates the creation of unusual dimeric structures and the adaptability of this approach is demonstrated through the introduction of 1,5-dialkoxynaphthalene (DAN) units. The unique arrangement of redox active moieties in this way allows intermolecular interactions to be investigated and their effect on each other’s electronic and magnetic properties to be probed. Demonstrated herein is that the pillar[5]arene-imidazole interaction can be used as a versatile motif in the synthesis of mechanically interlocked molecules with new and enhanced properties.